2002
DOI: 10.1186/1471-2172-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of ICAM-1, VCAM-1, MCP-1, and MIP-1α by spinal perivascular macrophages during experimental allergic encephalomyelitis in rats

Abstract: BackgroundT-cells extravasation and CNS parenchyma infiltration during autoimmune neurodegenerative disease can be evoked by local antigen presenting cells. Studying the chemoattracting potential of spinal perivascular macrophages (SPM) during experimental allergic encephalomyelitis (EAE), we observed numerous infiltrates of densely-packed mononuclear cells. Apart from the poor spatial and optical resolution, no differentiation between the resident SPM (mabs ED1+, ED2+) and the just recruited monocytes/macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Figure 2B shows a staining pattern for CCL2 that is closely associated with and branching out from the MBP lesion pattern displayed in red. The CCL2 seen here may have been generated by reactive astrocytes or perivascular macrophages [29] closely associated with nascent lesions, as in Figure 2A. The presence of DCs in areas expressing CCL2 (Figure 2C) suggests chemoattraction of these cells towards sites of lesion expressing CCL2.…”
Section: Resultsmentioning
confidence: 96%
“…Figure 2B shows a staining pattern for CCL2 that is closely associated with and branching out from the MBP lesion pattern displayed in red. The CCL2 seen here may have been generated by reactive astrocytes or perivascular macrophages [29] closely associated with nascent lesions, as in Figure 2A. The presence of DCs in areas expressing CCL2 (Figure 2C) suggests chemoattraction of these cells towards sites of lesion expressing CCL2.…”
Section: Resultsmentioning
confidence: 96%
“…The expressions of ICAM-1, VCAM-1 and MCP-1 were rapidly upregulated upon stimulation with the inflammatory factor LPS. The high expression of ICAM-1 enhances the adhesion of monocytes to endothelial cells, VCAM-1 can promote monocyte adhesion to endothelial cells, and monocyte chemotactic protein-1 (MCP-l) can activate monocytes by binding with receptors [ 55 , 56 ]. The current study revealed that Brazilian green propolis could reduce the expression levels of ICAM-1, VCAM-1 and MCP-1, in order to inhibit the migration of monocytes from the blood circulation to the intima of the blood vessels, reduce the aggregation of foam cells and lipids in the arterial wall, and inhibit the chemotaxis of monocytes to the lesion site, thereby reducing the accumulation of lipids in the intima and damage to the intima of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the recruitment of myeloid cells into the lumbar region occurs with concomitant increases in CCL2 and ICAM1 after spinal cord injury [52]. Activation of spinal perivascular macrophages is accompanied by the consistently increased expression of ICAM1 and the chemokine MCP-1 during experimental allergic encephalomyelitis [53]. Surprisingly, CCL2 has also been reported to negatively regulate ICAM1 expression and breast cancer metastasis [54].…”
Section: Discussionmentioning
confidence: 99%